Ciprofloxacin susceptibility of Salmonella enteric serovar Typhi and Paratyphi A from blood samples of suspected enteric fever patients - Adhikari, D; Acharya, D; Shrestha, P; Amatya, R (International Journal of Infection and Microbiology, 2012)
INTRODUCTION: Enteric fever caused by Salmonella enterica serovars Typhi and Paratyphi A is the common clinical diagnosis among febrile patients presenting to hospital in Nepal. The aim of this study was to evaluate the ciprofloxacin (CIP) and other antibiotics susceptibility patterns of Salmonella enterica serovars Typhi and Paratyphi A from blood samples of suspected enteric fever patients visiting KIST Medical College, Kathmandu. MATERIALS AND METHODS: Antibiotic susceptibility test was performed by Kirby Bauer disc diffusion method as per CLSI guidelines whereas MIC determination of ciprofloxacin was performed by agar dilution method. RESULTS: Altogether 64 presumptive Salmonella spp. were isolated from 840 blood samples of suspected enteric fever patients, of which 41 were S. Typhi and 23 were S. Paratyphi A. All Salmonella spp. isolates were sensitive to ceftriaxone and ofloxacin whereas 4 isolates were resistant to ciprofloxacin. One isolates each of S. Typhi and S. Paratyphi A were multidrug resistant. Fifty five isolates of Salmonella spp. were resistant to nalidixic acid (NA) with higher rate in S. Paratyphi A (91.3%) compared to S. Typhi (82.9%). MIC determination of ciprofloxacin revealed that majority of the isolates were resistant to ciprofloxacin and 2 isolates were resistant with MIC value of 4 µg/ml and 8 µg/ml. Importantly, we found simultaneous presence of NA resistance and decreased susceptibility to CIP suggesting that resistance to NA is a reliable indicator of decreased CIP susceptibility. CONCLUSIONS: Disc diffusion test failed to detect the reduced susceptibility of ciprofloxacin. Hence the MIC determination of ciprofloxacin against Salmonella spp. isolates would be important. DOI: http://dx.doi.org/10.3126/ijim.v1i1.6938 Int J Infect Microbiol 2012;1(1):9-13